2019
DOI: 10.1111/risa.13326
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Distributed Generators Resilience Considering Lifeline Dependencies During Extreme Events

Abstract: This article derives distributed generators resilience models considering lifeline dependencies during extreme events. The effects on power resilience of storage capacity, fuel delays, and fuel order placements are analyzed. Results indicate that storage capacity has an important role in improving overall power supply resilience as seen by loads. In addition, the presented models provide a quantifiable approach in evaluating fuel delivery resilience. The models facilitate studying fuel scheduling policies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Although batteries might still be able to service the cell site improving the resilience, typical battery backup times in cell sites are only a few hours (typically 4 h), which is a time scale much shorter than the expected duration of the event. Analysis with buffers at cell sites have also been performed but since this present work focuses on grid side modelling, instead of load side modelling, and the model of buffers requires a long discussion, such study has been left for a different publication found in [59]. The post-WMD grid dynamic simulation procedure is described as the following algorithm:…”
Section: Power Grid Resilience Model Integrationmentioning
confidence: 99%
“…Although batteries might still be able to service the cell site improving the resilience, typical battery backup times in cell sites are only a few hours (typically 4 h), which is a time scale much shorter than the expected duration of the event. Analysis with buffers at cell sites have also been performed but since this present work focuses on grid side modelling, instead of load side modelling, and the model of buffers requires a long discussion, such study has been left for a different publication found in [59]. The post-WMD grid dynamic simulation procedure is described as the following algorithm:…”
Section: Power Grid Resilience Model Integrationmentioning
confidence: 99%
“…Other prevention studies include Ouyang and Dueñas‐Osorio (2014) assessing the resilience of power systems in hurricane‐prone regions. Krishnamurthy and Kwasinski (2019) explored how distributed generators could be used to increase the resilience of critical infrastructure such as cell phone sites. Especially prominent in academic research are microgrid reliability evaluation and investment planning models.…”
Section: Introductionmentioning
confidence: 99%